The Influence Of Occupational Health Safety (K3) And Workload On Work Productivity (A Research On Employees Of Pt. Nata Bersaudara Sejahtera Tasikmalaya) - Fahda Aidatul Fitroh; Barin Barlian; Titin Patimah (Penerbit Jurnal Indonesia, 2023)
The purpose of this study is to determine the effect of Occupational Health Safety (K3) and Workload on the Work Productivity of employees of PT. Nata Bersaudara Sejahtera Tasikmalaya. The research method used is the Associative Quantitative approach to 83 respondents who are employees of PT. Nata Bersaudara Sejahtera Tasikmalaya. The types of data used are primary data and secondary data. The data analysis technique used is multiple linear regression analysis. The results of this test prove that occupational health safety (K3) has a partially insignificant effect.Workload has a partially significant effect on work productivity. Occupational Health Safety (K3) and Workload simultaneously have a significant effect on Employee Productivity at PT. Nata Bersaudara Sejahtera Tasikmalaya